Pengaruh Lokasi dan Fasilitas Terhadap Keputusan Pembelian Konsumen Pada Kedai Terapung Kecamatan Sape Kabupaten Bima - Abriansyah Abriansyah; Herry Nurdin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
This study aims to analyze the location and facilities of consumer purchasing decisions in the floating shop Sape District Bima Regency. The type of research used is associative using quantitative research. The research variables consist of: Location (X1) and Facilities (X2) as the independent variable, and Purchase Decision as the dependent variable (Y). All variables are used with a Likert scale. The number of samples issued was 96. Testing instruments using the validity test and reliability test. The data analysis tool used is multiple linear regression with SPSS version 16. The results of the study show the following regression lines: Y = 18,415-0,079X1 + 0,651X2 + e. The value of R (Correlation Coefficient) obtained was 0.694 or 69.4% and the value of R Square (Coefficient of Determination) was 0.421 or 42.1%. The results in this study indicate that the partial location does not determine the purchasing decision while the facility considers the purchasing decision. Together, it is proven from the location and the proven facilities towards the purchasing decision